Digital Media and the Return of the Representative Public Sphere - Trenz, Hans-Jörg (Javnost-The Public, 2009)
This article analyses how digital media redefine the boundaries of the political public sphere. Against the mainstream assumption of a new emancipatory potential of the digital media, which strengthens the participatory and interactive elements of the public sphere, it is argued that digital media introduce a new representative order of political communication. In this sense, there is a need to conceptualise the digital public sphere in relation to political representation. Digital media do not straightforwardly unbound political communication in replacing the representativeness of the national public sphere. The performance of the Internet in promoting political communication remains rather limited and, by and large, continues to reproduce the national public sphere. At the same time, the digital media have multiplied the symbolism of representation, which is continuously in the making, by providing new offers for the identification of publicness through shared problems and solutions.